2021
DOI: 10.1021/acs.jpcb.0c10403
|View full text |Cite
|
Sign up to set email alerts
|

Transesterification in Vitrimer Polymers Using Bifunctional Catalysts: Modeled with Solution-Phase Experimental Rates and Theoretical Analysis of Efficiency and Mechanisms

Abstract: Recently, thermoset vitrimer polymers have shown significant promise for structural applications because of their ability to be reshaped and remolded due to their covalent adaptive network (CAN). In these vitrimers, the transesterification reaction is responsible for the CAN, where the efficiency of the reaction is controlled either by organic or by organometallic catalysts. Understanding the mechanism of the transesterification reaction in the bulk phase using direct experimental techniques is extremely diffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 56 publications
0
37
0
Order By: Relevance
“…The contact of the dynamic bond with other associating groups might reduce the energy barrier for dissociation and in this way accelerate structural rearrangements. Catalysts can be introduced in vitrimers to reduce the activation energy, and this approach is used for many dynamic covalent bonds. In the associative exchange regime, the number of associated bonds (or dynamic cross-linking density) remains constant. Examples of these bonds include transamination, imine exchange, transesterification, boronic ester exchange, etc …”
Section: Models Describing the Behavior Of Polymers With Dynamic Bondsmentioning
confidence: 99%
“…The contact of the dynamic bond with other associating groups might reduce the energy barrier for dissociation and in this way accelerate structural rearrangements. Catalysts can be introduced in vitrimers to reduce the activation energy, and this approach is used for many dynamic covalent bonds. In the associative exchange regime, the number of associated bonds (or dynamic cross-linking density) remains constant. Examples of these bonds include transamination, imine exchange, transesterification, boronic ester exchange, etc …”
Section: Models Describing the Behavior Of Polymers With Dynamic Bondsmentioning
confidence: 99%
“…[48][49][50] However, computational studies at the atomic level using density functional theory to study the kinetics of the exchange reaction are scarce. 51 In this work, we aim to use density functional theory (DFT) calculations to render detailed information about exchange kinetics at the level of electrons, that is, the manifestation of electronic structures on the monomer scale, in the pursuit of promising candidates to develop new vitrimeric materials. The goal of the present study is twofold: first, the transamination exchange reaction mechanisms proposed in the literature for vinylogous urethanes will be analyzed and, second, a set of different vinylogous acyl compounds and free amines will be used to study the changes in the reaction mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical studies concerning vitrimers reported in the literature are mainly focused in coarse‐grained molecular dynamics simulations, which have been used to study and predict the effect of different parameters, such as the bond swap energy barrier and exchange rate, on the macroscopic properties of these materials 48–50 . However, computational studies at the atomic level using density functional theory to study the kinetics of the exchange reaction are scarce 51 …”
Section: Introductionmentioning
confidence: 99%
“…In each pathway, the carbonyl group may be activated by interaction of the O atom with a Brønsted or Lewis acid catalyst and possible additional assistance may be provided by proton relay molecules through H‐bond chains. One recent contribution has specifically addressed a model system of the metal‐catalyzed transesterification in vitrimers [19e] . A comparative investigation of the direct and two‐step pathways, with extensive analysis of the H‐bond chain assistance, has been presented for a mechanistically related reaction (the carbonate ester amination), [20] yielding activation barriers that are highly dependent on the number of proton relay molecules in the chain.…”
Section: Resultsmentioning
confidence: 99%